THE IDENTIFICATION FACTORS OF POOR PERFORMANCE OF INDONESIAN CIVIL STATE APPARATUS - Wirman Syafri (Jurnal Ilmiah Wahana Bhakti Praja, 2017)
The crucial issues face by Jokowi – JK  Administration is the poor performance of Indonesian civil state apparatus. The main objective of this research is to identify the main factors that lead to hamper the Indonesian civil state apparatus performance and to suggest recommendation on how to overcome the problem. Data is gathered from responses of selected informants through an interviewed and data analysis by triangulation analysis. The research finding the authority arrogance, intervention from others parties and managerial inability as a main factor of poor performance of Indonesian civil servant. This research highlights the importance of having strong commitment of manager, individual readiness, a good collaboration (solid team work) and independence of the state apparatus commission as a way out to overcome the problemKeyword: reform, performance,  state apparatus